MATERIAL FLOW ANALYSIS AND PLANT LAY-OUT OPTIMIZATION OF A MANUFACTURING SYSTEM - Longo, Francesco; Mirabelli, Giovanni; Papoff, Enrico (International Journal of Computing, 2014)
The paper proposes the results of a research project developed by the authors in collaboration with a production system working in the field of manufacturing wood products. The first step of the project was an accurate analysis of the system and the design of new production documents in order to collect data about the system itself. The collected data have been used to propose an initial solution of plant lay-out. The second step of the project was the construction of a simulation model. The model has been used to find an optimal plant- layout configuration by means of genetic algorithms with the goal of material handling cost and shop order flow time minimization.